Relations Between Husband and Wife in Child Rearing - Makhliyo, Tulkinboeva (Journal of Higher Education and Academic Advancement, 2024)
Every child has the right to live and be brought up in a family, to know his parents, to benefit from their care, to live with them. he has the right to be brought up by his side, to have his interests secured, to be fully developed, and to have his human values respected. The child has the right to visit his father, mother, grandfather, grandmother, brothers, sisters and other relatives. In the absence of the child's parents or when they are deprived of parental rights and in other cases when the child is deprived of parental care, the right to upbringing in the family is ensured by the guardianship and sponsoring body. Protection of the child's rights and legal interests is carried out by his parents (persons replacing them). If a minor is recognized as having full legal capacity in accordance with the law, he has the right to independently exercise his rights and obligations, including the right to protection.